Social Health Insurance for Developing Nations - Hsiao, William C.; Shaw, R. Paul (Washington, DC: World Bank, 2012)
Good health is necessary for well-being but also has another critical impact: it causes poverty, in that large health expenditures can bankrupt families. Many nations are now hoping that formally mandated social health insurance (SHI), involving payroll taxes, will provide a solution. This report examines the principles, design, and practices of SHI for low and middle-income nations and the necessary conditions for its viability and sustainability, with a focus on design and implementation issues. This volume presents five country case studies to provide evidence and greater detail on key issues that arise at different stages of implementation in low-income countries. They have been selected to reflect on a continuum and timeline of operational stages, beginning with the initial design and legislation of SHI, the first phase of implementation, the expansion to cover larger segments of the population, and on up to completion, whereby SHI becomes the predominant form of health care financing in a country. Accordingly, Kenya has been selected for illustration of the design stage, Ghana for initiation, the Philippines for extension of population coverage, Colombia for SHI and reform of health care delivery, and Thailand for universal coverage and reform of health care delivery. This sequencing and implied timeline of case studies allows this report to reflect on two questions. First, where can a country expect to be in relation to designing and implementing SHI in, say, 10 years? Second, as countries gain experience with SHI, what can they expect to offer or achieve in terms of variations in benefit design, who administers SHI, and how providers are contracted and paid?